2020
DOI: 10.1007/s00415-020-09766-8
|View full text |Cite|
|
Sign up to set email alerts
|

CT angiography vs echocardiography for detection of cardiac thrombi in ischemic stroke: a systematic review and meta-analysis

Abstract: Background and purpose Cardiac thrombi are an important cause of embolic stroke. We studied the diagnostic yield and diagnostic accuracy of cardiac CT angiography (CTA) compared to echocardiography for detection of cardiac thrombi in ischemic stroke patients. Methods We performed a systematic review and meta-analysis of the literature on cardiac CTA versus echocardiography for detection of cardiac thrombi in ischemic stroke patients. We included studies (N ≥ 20) in which both cardiac CTA (index test) and echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 32 publications
(56 reference statements)
0
39
0
Order By: Relevance
“…Performing TTE at this time is quicker than typically reported in other studies in stroke patients. 5,16,32 As our primary outcome we chose the diagnostic yield of cardiac CTA versus TTE, and not diagnostic accuracy of CTA versus TTE. We did so because we believe that due to the lack of a true gold standard for many cardio-aortic sources of embolism, presenting results in terms of sensitivity/specificity does not necessarily reflect the truth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Performing TTE at this time is quicker than typically reported in other studies in stroke patients. 5,16,32 As our primary outcome we chose the diagnostic yield of cardiac CTA versus TTE, and not diagnostic accuracy of CTA versus TTE. We did so because we believe that due to the lack of a true gold standard for many cardio-aortic sources of embolism, presenting results in terms of sensitivity/specificity does not necessarily reflect the truth.…”
Section: Discussionmentioning
confidence: 99%
“…Performing TTE at this time is quicker than typically reported in other studies in stroke patients. 5 , 16 , 32 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early CTA screening could carry therapeutic implications by identifying a possible embolic source. Previous studies showed that implementation of CTA of the heart and aorta is a feasible alternative to TEE for identification of CE sources, 12 however, these studies either included patients with a high probability for having CE sources (e. g. suspected embolic stroke or AF), 4,10,13À17 or did not include patients with suspected TIA. 18À20 The objective of this study was therefore to investigate the yield and the therapeutic implications of CTA of the heart and aorta in patients presenting with TIA or IS without a specific high probability for CE sources.…”
Section: Introductionmentioning
confidence: 99%